α-Glucosidase Inhibitory Activity of Triglycerides and Methyl Linoleate of Murraya koenigii Spreng from Malaysia - Noor Hazlina Ibrahım; Mohd Azlan Nafiah; Muhammad Hafiz Husna Hasnan; Supriatno Salam; Siow-Ping Tan; Tarso Rudiana (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2026)
This study was designed to examine the α-glucosidase inhibitory activity of triglycerides and methyl linoleate isolated from the root extract of Murraya koenigii Spreng in Malaysia. Although M. koenigii has been widely reported for its medicinal properties, few studies have examined the α-glucosidase inhibitory activity of its isolated lipid compounds, particularly triglycerides and methyl linoleate. The chemical compounds were obtained by cold extraction with various solvents and purified by chromatographic techniques, including NMR, MS, and IR analyses. Antidiabetic activity was evaluated using an α-glucosidase inhibitory assay. The results of these studies indicated that triglyceride (1) (IC50 = 33.6 ± 0.05 µg/mL) from the hexane crude extract and methyl linoleate (2) (IC50 = 13.9 ± 0.19 µg/mL) from the methanol crude extract exhibited potent inhibitory activity in the α-glucosidase inhibitory assay. The results showed that root extracts of M. koenigii exhibit significant antidiabetic activity, which may help identify new chemical classes of natural antidiabetic substances.